1993
DOI: 10.1007/bf02266993
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of esophageal motility disorders

Abstract: Swallowing is a complex mechanism that is based on the coordinated interplay of tongue, pharynx, and esophagus. Disturbances of this interplay or disorders of one or several of these components lead to dysphagia, non-cardiac chest pain, or regurgitation. The major esophageal motility disorders include achalasia, diffuse esophageal spasm, hypercontractile esophagus ("nutcracker esophagus"), and hypocontractile esophagus ("scleroderma esophagus"). Other esophageal diseases such as hypopharyngeal (Zenker's) diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This is clinically relevant especially in patients with weak peristalsis, and Shaker et al [7] have shown that the absence of a reserve in patients referred for anti-reflux surgery predicts post-surgical dysphagia. Furthermore, as it has been reported that prokinetic drugs lead to disappointing results in patients with weak peristalsis [17], ongoing studies are testing the hypothesis that the presence of a motor reserve at MRS identifies patients who may benefit from such drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This is clinically relevant especially in patients with weak peristalsis, and Shaker et al [7] have shown that the absence of a reserve in patients referred for anti-reflux surgery predicts post-surgical dysphagia. Furthermore, as it has been reported that prokinetic drugs lead to disappointing results in patients with weak peristalsis [17], ongoing studies are testing the hypothesis that the presence of a motor reserve at MRS identifies patients who may benefit from such drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients can take these medications without the knowledge of their physician and can purchase them without a prescription, it is likely that we did not identify all users. The antihypertensive medications examined in this study might sometimes be used to treat conditions that might be related to GI tract bleeding (eg, calcium channel blockers for esophageal motility disorders 18 and ␤-blockers for esophageal varices 19 ). However, all subjects in this study were being treated for hypertension, and these additional indications would be expected to be relatively uncommon.…”
Section: Commentmentioning
confidence: 99%
“…Nutcracker esophagus often responds well to calcium channel blockers such as nifedipine [Richter et al, 1987]. Other treatments include nitrates, anticholinergic drugs, sedatives, and surgery [Allescher and Ravich, 1993;Feussner et al, 1993]. Nutcracker esophagus is not well described in children.…”
Section: Discussionmentioning
confidence: 98%